Analysis of Posterior Tibial Slope as Risk Factor to Anterior Cruciate Ligament Tear - de Sousa Filho, Pedro Guilme Teixeira (Rev Bras Ortop (Sao Paulo), 2021)
Objective  The objective of the present study was to evaluate the relationship between patients with anterior cruciate ligament (ACL) injury by indirect trauma and increased posterior tibial inclination. Methods  Retrospective study, performed by analysis of medical records and digital radiographs of patients, present in a database of a tertiary orthopedic hospital. The sample consisted of two groups, the first group consisting of patients diagnosed with ACL injury by indirect trauma, and a control group matched by age. Results  Each group consisted of 275 patients, whose measurements of posterior tibial inclination were measured by three specialists. It was observed that the group of patients with ACL lesion presented a significantly higher tibial slope (in degrees) than the control group in the total sample and in the subsamples stratified by gender. The best cutoff point for the first group was identified as a posterior tibial inclination ≥ 8°, achieving a sensitivity of 63.3% and a specificity of 62.5%. The first group also had a tibial slope ratio ≥ 8° (63.3%), significantly higher than the control group (37.5%), with an odds ratio of 2.8. Conclusion  It was concluded that the increase of the posterior tibial inclination is associated with an increased risk for injury of the ACL by indirect trauma, mainly for values ≥ 8°.